Particulate organic carbon in the deep-water region of the Gulf of Mexico - Yéssica Vanessa Contreras-Pacheco; Sharon Z. Herzka; Gerardo Vallejo-Espinosa; Juan Carlos Herguera (Frontiers in Marine Science, 2023)
Ocean eddies play a major role in lateral and vertical mixing processes of particulate organic carbon (POC), as well as in the transport of heat, salinity, and biogeochemical tracers. In the open waters of the Gulf of Mexico (GoM), however, there are limited observations to characterize how these mesoscale structures affect the spatial distribution of POC in the upper water column, which is important for organic matter cycling and export. We present the distribution patterns of POC relative to mesoscale features throughout the water column in the deep-water region of the GoM during three oceanographic cruises held during the summer months of 2015, 2016, and 2017. Samples were collected under well-stratified upper ocean conditions, which allowed us to assess the spatial and temporal distribution of POC as a function of non-steric sea surface height, density, apparent oxygen utilization, and chlorophyll fluorescence. We further explored the variability of integrated surface layer POC concentrations at stations located within the cores and the edges of cyclonic and anticyclonic eddies, and those collected outside these structures. Although our results indicate mesoscale eddies modulate several important physical and biogeochemical variables and POC concentrations in the upper ocean, these features do not fully explain the spatial distribution of POC concentrations throughout the deep-water region of the GoM. Relatively lower POC concentrations were observed in the border of the cyclonic and the center of the anticyclonic eddies, in contrast to the relatively higher POC concentrations at the center of the cyclonic and the border of anticyclonic eddies. We observed high variability in POC concentration variability outside mesoscale structures, which may be attributed to other processes such as upwelling over the shelves, and the contribution by rivers during the summer especially in the northern and southern GoM.